Chemical profiles of Terminalia catappa LINN nut and Terminalia subspathulata KING fruit - Yakubu, Yahaya; Lee, Soo Yee; Shaari, Khozirah (Universiti Putra Malaysia Press, 2021)
Terminalia catappa and Terminalia subspathulata are two species of the Combretaceae family of medium to large forest trees. The fruits of T. catappa are known for the edible nuts commonly known as tropical almonds due to their similarity in taste with almonds of commerce. Therefore, the chemical profiles of the fruits of the two Terminalia species were examined to ascertain their potential value for food or health uses. Gas chromatographymass spectrometry (GCMS) and ultrahigh-pressure liquid chromatography-electrospray ionisation tandem mass spectrometry (UHPLC-ESI-MS/MS) techniques were employed to profile the extracts to ensure good coverage of the classes of metabolites of the fruit extracts. The GCMS results revealed that T. catappa nuts were rich in palmitic acid (33.2%), linoleoyl chloride (29.1%), and oxacyclohexadecan-2-one commonly known as pentadecanolide (16.2%). In comparison, the major constituents of T.subspathulata fruits were palmitic acid (18.1%) and its methyl ester, methyl palmitate (9.3%). Furthermore, a total of 38 compounds were putatively identified in the 70% aqueous methanolic extracts of both species via UHPLC-ESI-MS/MS analysis, comprising three organic acids, sixteen hydrolysable tannins, ten phenolic acids, eight flavonoids, and a diarylheptanoid. The GCMS- and liquid chromatography-mass spectrometry- (LCMS-) LCMS-based metabolite profiles obtained in the present study have revealed the diversity of chemical constituents in the T. catappa nuts and T. subspathulata fruits, potentially valorised as functional foods nutraceutical ingredients for plant-based health products.